A contemporary standards-based evaluation of Arabic language teaching methods in grade eight Arabic schools in Brunei Darussalam - Yani, Achmad; Haji Ahmad, Siti Sara; Haji Abdullah, Hajah Rafidah; Mohamed Abdelgelil, Mohamed Fathy; Seff, Faisal Mubarak; Sahrir, Muhammad Sabri; Haji Abdul Kahar, Kujaimah; Mohamed Mousa, Abdelnaser Abdelgalil; Husain, Muhammad Zakir; Haji Abdullah, Hajah Rafizah (WSEAS Press, 2026)
This field-based study aimed to evaluate the methods used in teaching Arabic to eighth-grade students in Arabic schools in Brunei Darussalam in light of contemporary standards in language education, through the analysis of quantitative data interpreted with qualitative support. The study adopted an evaluative-analytical approach to examine the extent to which actual classroom practices align with the principles of communicative competence, which emphasize that language learning is not confined to grammatical knowledge alone, but extends to the ability to use language effectively in authentic communicative contexts (Canale & Swain, 1980, pp. 1–47). The findings revealed that the current instructional reality is characterized by a hybrid structure that combines deeply rooted traditional practices with emerging indicators of communicative pedagogy. On the one hand, the heavy reliance on translating Arabic texts into Malay remained strikingly high, reaching 84.1%, which indicates the continued centrality of translation in classroom practice. On the other hand, the data also demonstrated positive tendencies toward the adoption of certain communicative principles, including methodological variety (81.0%), attention to communicative competence (76.6%), and relatively strong emphasis on training students in the four language skills. However, the findings also disclosed a clear gap between teachers’ declared pedagogical orientations and students’ actual communicative performance. While teachers reportedly encouraged the use of Arabic, the proportion of students speaking Arabic with their peers declined to only 40.1%, indicating the limited presence of Arabic interaction within the classroom community. This finding corroborates the contemporary literature, which argues that the success of communicative language teaching depends on an interaction-rich classroom environment, dense exposure to meaningful input, and authentic opportunities for linguistic production (Nation, 2007, pp. 2–13; Littlewood & Yu, 2011, pp. 64–77). The study concludes that Arabic language teaching in this context remains in a transitional phase between the traditional structural model and the modern communicative model. It therefore recommends strengthening the use of Arabic as the principal medium of instruction, expanding interactive classroom activities, and aligning assessment practices and instructional content with contemporary global standards in language education